Colonic agenesis with anorectal malformation - Rarest variant of congenital short colon - Rashi Rashi; Amit Kumar; Ram Jeewan Singh; Shreyas Dudhani; Amit Kumar Sinha; Bindey Kumar (Wolters Kluwer Medknow Publications, 2022)
We report a case of colonic agenesis with anorectal malformation in a newborn girl. The patient also presented with congenital heart disease. We are presenting the clinical features, intraoperative findings, and treatment plan.